Model predictive control of temperature and humidity of artificial climate chest based on neuro dynamical optimization - Peng, Fei; Peng, Yonggang; Wei, Wei (Nong ye gong cheng xue bao, 2014)
Because an artificial climate chest can provide an artificial climate environment, it is widely used in biological, chemical, and agricultural science experiments. In this paper, model predictive control (MPC) was used to control the temperature and humidity of an artificial climate chest. Online optimization is one of key problems of MPC. The temperature and humidity object of an artificial climate chest is an object with two inputs and two outputs, and the object has the characteristics of time delay and coupling. Based on the model of the temperature and humidity of an artificial climate chest, the MPC method and optimization model of an input delay object were derived. First, the temperature and humidity object of an artificial climate chest were described in state equations form. Secondly, an optimization problem in the MPC of an artificial climate chest was proposed. Simulation results showed that this method had smaller overshoot and higher control accuracy than the PID method.